A comparison of the glycemic index of sorghum and other commonly consumed grains - Pruett, Ashley (Kansas State University, 2012)
Little in vivo research on glycemic index (GI) values or the digestive impact of sorghum based food products currently exists. Because sorghum is a gluten-free grain, its utilization in the United States is growing, especially in baking applications. Information on how sorghum affects blood sugar levels would be beneficial as new products emerge because glycemic effect has an impact on human health and in controlling diabetes. The objective of this study was to determine the GI of a sorghum muffin, and compare this value to the GI of muffins made from commonly consumed grains in the United States. The effects of particle size and damaged starch on GI were also studied. GI values were determined for muffins made from white sorghum, corn, brown rice, whole wheat, and all-purpose flours. All muffin formulations were composed of flour, water, baking powder and salt. To determine the GI, weighed portions of muffin containing 20g of available carbohydrates were eaten on separate occasions by eight healthy volunteers (ages 18-40) after an overnight fast (10 hours). Each muffin was administered twice. Two capillary blood samples were taken at 0 (fasting), 30, 45, 60, 90 and 120 minutes after consumption and averaged. Blood glucose curves were constructed from mean blood glucose values. The GI was calculated by dividing the incremental area under the curve for the test food (muffin) by that for the standard (20g dextrose drink) and multiplying by 100. The GI for the muffins was calculated as the mean from the respective average GIs of the 8 volunteers. The data indicated that sorghum flour milled at particle size < 400 um resulted in the lowest GI of 32 ± 16.8. These findings should assist in development of lower GI sorghum foods.
Keywords: Glycemic Index; Sorghum; Food Science (0359); Nutrition (0570)